2018
DOI: 10.1139/cjpp-2017-0245
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with morphine protects hippocampal CA1 neurons from ischemia–reperfusion injury via activation of the mTOR pathway

Abstract: The signaling pathway of chronic morphine treatment to prevent neuronal damage following transient cerebral ischemia is not clear. In this study, we examined the role of mammalian target of rapamycin (mTOR) to identify the neuroprotective effects of chronic morphine preconditioning on the hippocampus following ischemia-reperfusion (I/R) injury. Morphine was administered for 5 days, twice a day, before inducing I/R injury. The possible role of mTOR was evaluated by the injection of rapamycin (5 mg/kg body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…In addition, morphine protected PC12 cells against the cytotoxicity of 1-methyl-4phenylpyridinium through activating phosphatidylinositol 3-kinase (PI3K)/Akt pathway (Fan et al, 2019). Some groups demonstrated that preconditioning with morphine alleviated cerebral ischemia injury through activating the mTOR pathway (Arabian et al, 2018b) or mitochondrial KATP channels (Arabian et al, 2018a). However, repeated use of morphine will lead to various sideeffects, such as antinociceptive tolerance, dependence, and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, morphine protected PC12 cells against the cytotoxicity of 1-methyl-4phenylpyridinium through activating phosphatidylinositol 3-kinase (PI3K)/Akt pathway (Fan et al, 2019). Some groups demonstrated that preconditioning with morphine alleviated cerebral ischemia injury through activating the mTOR pathway (Arabian et al, 2018b) or mitochondrial KATP channels (Arabian et al, 2018a). However, repeated use of morphine will lead to various sideeffects, such as antinociceptive tolerance, dependence, and addiction.…”
Section: Introductionmentioning
confidence: 99%
“…TT interferes with subsequent spermatogenesis in 50% of patients and impairs borderline in another 20% (Visser & Heyns, ). Manual detorsion is successful in >80% of attempts, but reperfusion may cause a sequential chain of the pathophysiological effects, including massive intracellular Ca 2+ release, recruitment of neutrophils, acute inflammatory responses and generation of reactive oxygen species (ROS) that increases apoptotic or necrotic cell death (Ajami et al., ; Amani et al., ; Arabian et al., ; Cayan et al., ; Güneş et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven days after cerebral ischemic injury, a passive avoidance test was conducted to assess memory performance in rats. The procedure was executed by using shuttle box according to the method described by Arabian et al (2017). Primarily, the animals were placed in the shuttle box to habituate with the surrounding.…”
Section: Passive Avoidance Testmentioning
confidence: 99%